The Addition of Honey Bee to The Feed for Increase The Growth of White Snapper Seeds (Lates calcarifer) - Linayati Linayati; Bramantiar Rizkyansyah; Tri Yusufi Mardiana; Muhammad Zulkham Yahya (Department of Aquaculture, 2021)
The purpose of this study was to determine the effect of adding honey to the feed for growth and the best dosage for the growth of white snapper seeds.The white snapper seeds used have an average weight of ± 2.5 g / fish.This study used an experimental method with a Completely Randomized Design (CRD).The experiment was carried out in 5 (five) treatments and each treatment had 3 (three) repetitions.The treatment consisted of adding honey to the feed with a treatment dose of (A) 0 ml / kg of feed, (B) 50 ml / kg of feed, (C) 100 ml / kg of feed, (D) 150 ml / kg of feed and (E) 200 ml / kg of feed.The results indicated that the addition of honey to the feed had a significant effect on the growth of white snapper seeds.The best dose of honey is at a dose of 200 ml / kg which has the best effect on fish growth.The condition of water quality during the study was in a suitable range for the life of white snapper seeds.